2002
DOI: 10.1038/sj.bmt.1703614
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus reactivation with clinical flare in allogeneic stem cell transplants with chronic graft-versus-host disease

Abstract: Summary:We conducted a retrospective study with the aim of identifying risk factors and clinical characteristics associated with HBV reactivation and clinical flare after allogeneic stem cell transplantation (aSCT). We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 47 publications
4
73
0
Order By: Relevance
“…9 In the present study, four patients had extensive cGVHD, and three of them showed reverse seroconversion. Only one patient with extensive cGVHD showed no evidence of viral reactivation (ID 6): she was the only recipient of stem cells from a vaccinated donor, but also the patient with the shortest follow-up (15 months).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…9 In the present study, four patients had extensive cGVHD, and three of them showed reverse seroconversion. Only one patient with extensive cGVHD showed no evidence of viral reactivation (ID 6): she was the only recipient of stem cells from a vaccinated donor, but also the patient with the shortest follow-up (15 months).…”
Section: Discussionmentioning
confidence: 93%
“…8,9 This difference could be explained by a variety of reasons: (i) In our study -as in others -the risk had to be estimated from a small number of available allo-HSCT patients with pretransplant anti-HBs and anti-HBc antibodies; (ii) detection of HBV reactivation might be missed in the absence of clinical symptoms. In the present study, only one of three patients with reverse seroconversion had biochemical signs of liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…21 The rituximab ϩ steroid-containing chemotherapy has recently been demonstrated to be a risk factor for HBV reactivation in HBsAgnegative patients, 5,6 HBV reactivation is a well-known complication after allogeneic hematopoietic stem cell transplantation (HSCT) because of the long-term use of immunosuppressive drugs and the gradual immune reconstitution after HSCT. 22,23 Additional host risk factors for HBV reactivation have been reported as male sex, 6 diagnosis of lymphoma, 3 absence of anti-HBs at baseline, 6,24 and decrease of anti-HBs titers after immunosuppressive therapy. 25 The risk classification for HBV reactivation according to serum HBV markers and the intensity of immunosuppressive therapy can be determined based on the current evidence ( Figure 1).…”
Section: Risk Of Hbv Reactivation After Immunosuppressive Therapymentioning
confidence: 99%
“…[39][40][41][42][43][44][45][46][47][48][49][50] Based on reported series, 47,[51][52][53][54] the frequency of seroreversion ranges between 14% and 50% (Table 1A). The wide range reported could be explained by risk estimation based on small series, missed cases of seroreversion due to absence of symptoms, and variable duration of posttransplant follow-up.…”
Section: Reactivation Inmentioning
confidence: 99%